Halal MSME Sustainability: Digital Marketing, Innovation, and Islamic Economics Synergy - Hendro Sukoco; Ade Yuliana; Sinta Anggraeni; Melli Andini (Universitas Negeri Semarang, 2025)
This study examines the effects of digital marketing strategy and halal innovation on the sustainability of halal micro, small, and medium enterprises (MSMEs), with Islamic economic implementation as a mediating variable and Sustainable Development Goals (SDGs) orientation as a moderating variable. The research was conducted among 160 halal-certified MSMEs in six regions of Central Java (Banyumas, Purbalingga, Banjarnegara, Cilacap, Kebumen, and Brebes), using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings provide mixed empirical support. Halal innovation demonstrates a positive and statistically significant effect on MSME sustainability. In contrast, the digital marketing strategy shows a positive but statistically insignificant direct relationship. Islamic economic implementation plays a limited, marginal mediating role in the relationship between halal innovation and sustainability. Furthermore, SDGs orientation does not significantly moderate the proposed structural relationships. These results suggest that halal innovation serves as the primary driver of sustainability. In contrast, digitalization and alignment with global sustainability appear not yet strongly embedded in the strategic practices of the sampled halal MSMEs. The study contributes by clarifying the empirical boundaries of integrating digital strategies, halal innovation, and Islamic economic values within MSME sustainability frameworks in emerging economies